Molecular characterization and genogrouping of Classical Swine Fever Virus isolated from field outbreaks - chakraborty, sandip paritosh; VEEREGODA, B M; CHANDRA NAIK, B M; RATHNAMMA, D; ISLOOR, S; VENKATESHA, M D; LEENA, G; VEERESH, H; PATIL, S S (The Indian Journal of Animal Sciences, 2011)
Â The aim of the present study is to characterize Classical Swine Fever Virus (CSFV) isolated from field outbreaks in suburban places of Bangalore, India, using molecular techniques and subsequent genogrouping of the virus. Various tissue samples from CSFV affected pigs (n=12) were collected and subjected to either virus isolation in PK-15 cell line, or RNA extraction. PCR amplification was carried out targeting the 5’ NTR gene following commercially available RT-PCR kit protocol. Subsequent agarose gel electrophoresis yielded specific amplicons of 421 bp obtained from pooled samples of three pigs. The PCR purified products were sequenced and subjected to BLAST analysis and subsequently submitted to GenBank. The obtained nucleotide sequences were aligned using MegAlign programme and further subjected to analysis using MEGA 4 programme. All three field isolates were found to be grouped into subgroup 2.2 of group 2. Â